2014
DOI: 10.1007/s00383-014-3628-1
|View full text |Cite
|
Sign up to set email alerts
|

Disorders of sex development in a developing country: perspectives and outcome of surgical management of 39 cases

Abstract: There is a wide spectrum of DSD in our setting. Time to diagnosis, evaluation, and outcome may be improved by public enlightenment initiative, focused education of healthcare personnel and provision of relevant diagnostic facilities through enhanced funding and collaboration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…The challenges highlighted included late patient presentation, inadequate facilities to make an accurate diagnosis, sociocultural influence of the African community, and loss to follow-up. Similar challenges have been noted in other centers within Sub-Saharan Africa (16). Africa has unique sociocultural influences.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The challenges highlighted included late patient presentation, inadequate facilities to make an accurate diagnosis, sociocultural influence of the African community, and loss to follow-up. Similar challenges have been noted in other centers within Sub-Saharan Africa (16). Africa has unique sociocultural influences.…”
Section: Discussionsupporting
confidence: 59%
“…In the present study, the median age at presentation was 6.5 years. Other authors have reported similar delays in presentation, some as late as adolescence (16).…”
Section: Discussionsupporting
confidence: 56%
“…2,14 This is in contrast to most large Western series of DSD in which CAH was documented as the most common DSD 15,16 and also differs from previous studies in Nigeria. 3,4 In a review of DSD cases from 60 centers in 23 European countries, Pasterski et al 17 reported that Turner syndrome and CAH comprised 22.3% and 20.1%, respectively, of the total DSD cases. In Thailand, Turner syndrome and 21-OH deficiency CAH were also the 2 most common disorders of all DSD cases, occurring in 36.8% and 23.9% of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the present report, the number of neonatal surgical cases and their distribution might not be a true reflection of the actual incidence in our setting. As some previous studies have indicated, some of these cases do not come to the attention of the mainstream care facility as a result of sociocultural factors, ignorance and poverty.…”
Section: Discussionmentioning
confidence: 96%